2009
DOI: 10.3354/ab01310
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial activity and diffusive nutrient supply in the oligotrophic Central Atlantic Ocean

Abstract: Growing evidence of inorganic nutrient limitation on oceanic bacteria suggests a global dependence of bacterial activity and production on rates of nutrient supply. The present study examined whether surface bacterial abundance is significantly related to water column stability, and whether bacterial activity and growth rate are related to the rate of diffusive supply of inorganic nutrients to the mixed layer in the Central Atlantic during 2 meridional cruises. The 2 cruises were run under very different ocean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 61 publications
(46 reference statements)
3
13
0
Order By: Relevance
“…Indeed, previous studies performed in tropical estuarine waters showed lower BR rates (BR max =0.7 µM C h LEE et al, 2009;RAM et al, 2003). Nutrient availability also plays a major role in regulating bacterial carbon metabolism (ASMALA et al, 2014;BERGGREN et al, 2010;GASOL et al, 2009;KEMP, 2003). Bacterial uptake of DOM follows a rather constant ratio: C:N:P ~ 50:10:1 (FAGERBAKKE et al, 1996;GOLDMAN et al, 1987).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, previous studies performed in tropical estuarine waters showed lower BR rates (BR max =0.7 µM C h LEE et al, 2009;RAM et al, 2003). Nutrient availability also plays a major role in regulating bacterial carbon metabolism (ASMALA et al, 2014;BERGGREN et al, 2010;GASOL et al, 2009;KEMP, 2003). Bacterial uptake of DOM follows a rather constant ratio: C:N:P ~ 50:10:1 (FAGERBAKKE et al, 1996;GOLDMAN et al, 1987).…”
Section: Discussionmentioning
confidence: 99%
“…Similar patterns were described by Corno et al (2007), who used lower euphotic zone stratification to describe patterns in the composition of the picoplankton community at the ALOHA time-series station. As far as we know, previous studies that focused on the relationship between bacterial abundance and nutrient supply are limited to the study by Gasol et al (2009), who described a positive relationship between water column stratification and heterotrophic bacterial abundance.…”
Section: The Use Of Proxies For Estimating Nutrient Supplymentioning
confidence: 99%
“…1B & 1C in Table 4), indicating a lower response of bulk bacterial abundance to increasing phytoplankton biomass in oligotrophic conditions (i.e. Gasol & Duarte 2000, Gasol et al 2009). Whilst bacterial community structure was not analyzed in these previous studies, one can consider that such low slopes found at the bulk level in offshore systems may indicate that the bacterial groups exhibiting similar weak regression slopes would be those mainly driving the relationship.…”
Section: Bcs−chl a Relationships In Coastal And Open-ocean Conditionsmentioning
confidence: 99%
“…This would in turn support the idea proposed by Yokokawa & Nagata (2005) that particular ecological traits (DOC uptake, bacterial production and growth, grazing rates) can be detected using broad phylogenetic probes, when an ecological trait of a broad group largely reflects the trait of the dominant subgroup in the community. Low coupling between SAR11 and chl a might also indicate the use by this dominant bacterial group in oceanic waters of non-contemporaneous primary production, something that has been suggested to occur for the bulk community across the central Atlantic gyre (Gasol et al 2009). …”
Section: Bcs−chl a Relationships In Coastal And Open-ocean Conditionsmentioning
confidence: 99%